Postoperative Migration of an Edwards-SAPIEN XT Mitral Valve-in-Valve Treated With Direct Vision Implantation During Beating-Heart Bypass - Mick, Stephanie L.; Roselli, Eric E.; Kapadia, Samir; Tuzcu, E. Murat; Krishnaswamy, Amar; Svensson, Lars G. (The Annals of thoracic surgery, 2016)
Transcatheter valve-in-valve mitral valve replacement provides treatment options to high-risk patients but is subject to its own complications. We present the migration of a transcatheter balloon-expandable Edwards-SAPIEN XT valve (Edwards Lifesciences, Irvine, CA) within a previously implanted surgical Carpentier-Edwards valve (Edwards Lifesciences) and our novel approach to its treatment.